Experience of an Egyptian tertiary Laboratory in the diagnosis of tuberculous and non-tuberculous Mycobacterial Infections: A five-year retrospective study. - Asmaa Ramadan; Sherine Shawky; Arsany Ibrahem; Mohammed El-Kholy (Microbes and Infectious Diseases)
Background: Tuberculosis (TB) is one of the significant health concerns in Egypt, necessitating rapid, affordable, and accurate diagnosis to aid in its control. This study presents data collected over five years (2017-2021) to explore different diagnostic TB methods in our lab. Methods: A total of 33700 non-repetitive samples were subjected to different diagnostic methods; 30000 were stained by Ziehl–Neelsen (ZN), of which 2819 were cultured on Löwenstein-Janssen (LJ) media, and 456 were analyzed by GeneXpert; 3700 samples were tested by interferon-gamma release assay (IGRA) Quantiferon. Moreover, 3650 patients underwent the tuberculin skin test (TST). Results: GeneXpert displayed the highest positivity (23.9%), while ZN smear microscopy was the lowest (4.8%). The detection capability between pulmonary and extrapulmonary samples was not statistically significant using LJ culture but significant using GeneXpert MTB/RIF. Rifampicin resistance was 17.4% among the GeneXpert Mycobacterium tuberculosis (MTB)-positive samples. Conclusions: GeneXpert MTB/RIF assay is a user-friendly, rapid, and efficient method for identifying pulmonary and extrapulmonary TB with the simultaneous detection of rifampicin-resistant strains. However, culture and smear microscopy remain the most dominant diagnostic methods in developing countries due to their low cost and relatively acceptable specificity.